Chemical castration in dogs by the intra-epididymal application of sclerosing substances - Goicochea Vargas, José (2020)
The clinical effects, sperm parameters and macroscopic and histological lesions caused by chemical castration in dogs through the application of sclerosing substances were evaluated. Three groups were established: (G1, n=10), 4% chlorhexidine gluconate, (G2, n=10), 4% benzalkonium chloride + 0.4% cetrimide, and (G3, control, n=5) chloride of 0.9% sodium, at a dose of 0.5-1.0 ml intra-epididymal (IEPD) and bilateral on day 0. The effects were evaluated on days 2, 7, 14, 28 and 56 post-application. The manifest oligospermia was observed in 9/10 animals of G1 (90%) and in 7/10 of G2 at day 2 post-application, with a critical decrease of sperm concentration (3.78 ± 6.3 x 106/ml and 0.95 ± 0.89 x 106/ml, respectively, motility of 0.10 ± 0.32 - 0.20 ± 0.42% with oscillatory movement, without progressive advance and vitality of 0.30 ± 0.67% - 0% in both groups. Azoospermia was detected in all ejaculates of both groups from day 28, while sperm variables were normal in the dogs of the control group. The macro and microscopic changes were hydrocele, intra and extratubular haemorrhage, destruction and necrosis of the tubular wall, being more severe in G2, atrophy of the seminiferous tubules with replacement of fibrotic tissue, cysts and formation of spermiogranulomas from day 7 on G2 and G1. Chemical castration is considered an alternative for mass sterilization in dogs.